(untitled) (Research, Society and Development, 2024)
Introduction: The use of social media is strongly linked to a high prevalence of body image dissatisfaction, eating disorders, and body modification behaviors among adolescents. Objective: This study aims to test a biopsychosocial model to evaluate the influence of social media use on body image dissatisfaction and inappropriate behaviors related to eating and muscle-building, according to the gender and age of Brazilian adolescents. Method: 304 adolescents (60.2% female), aged between 12 and 16 years (13.8±0.81 years), participated in the study. Descriptive statistics were computed, and the correlations among study variables were examined separately for boys and girls. The model was tested using Path Analysis. The model fit was evaluated using the Comparative Fit Index (CFI), Global Fit Index (GFI), and Root Mean Square Error of Approximation (RMSEA). Analyses were conducted using the Jamovi statistical software. Results: The test of the hypothetical model, after modification indices adjustments, revealed a good fit to the data, although differences in pathways were observed between boys and girls. Conclusion: We conclude that the tested biopsychosocial model is suitable for assessing the relationships between social media use, body image dissatisfaction, eating restriction behaviors, and muscle-building behaviors among Brazilian adolescents of both sexes.